2016
DOI: 10.1371/journal.pntd.0004492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two or Six Doses 800 mg of Albendazole Every Two Months on Loa loa Microfilaraemia: A Double Blind, Randomized, Placebo-Controlled Trial

Abstract: BackgroundLoiasis is a parasitic infection endemic in the African rain forest caused by the filarial nematode Loa loa. Loiasis can be co-endemic with onchocerciasis and/or lymphatic filariasis. Ivermectin, the drug used in the control of these diseases, can induce serious adverse reactions in patients with high L loa microfilaraemia (LLM). A drug is needed which can lower LLM below the level that represents a risk so that ivermectin mass treatment to support onchocerciasis and lymphatic filariasis elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
1
23
2
Order By: Relevance
“…Although high dose ALB (400 mg twice daily) for 3 weeks induced scrotal reactions in 11 of 15 men in one study (compared to zero of 13 DEC-treated men) [ 59 ], there is no evidence that adding single-dose ALB to IVM or DEC for LF MDA increases AEs [ 5 ]. In areas where LF is co-endemic with loiasis, semiannual ALB alone (together with integrated vector management) is recommended for LF MDA, because ALB can be safely given to persons with loiasis [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although high dose ALB (400 mg twice daily) for 3 weeks induced scrotal reactions in 11 of 15 men in one study (compared to zero of 13 DEC-treated men) [ 59 ], there is no evidence that adding single-dose ALB to IVM or DEC for LF MDA increases AEs [ 5 ]. In areas where LF is co-endemic with loiasis, semiannual ALB alone (together with integrated vector management) is recommended for LF MDA, because ALB can be safely given to persons with loiasis [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study recorded no significant change in parasite loads in any of the treatment groups. Another study tested different intermittent doses of albendazole on Loa loa microfilaraemia, the reduction in mf load obtained was insufficient to prevent the risk of severe adverse reactions during ivermectin mass drug administration in loiasis co-endemic areas [ 21 ]. These observations demonstrated that repurposing of existing antiparasitic therapies may not be a suitable approach to develop drugs with satisfactory therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…This group consisted of individuals tested positive with Loa loa microfilariaemia of greater than or equal to 30,000 mf/ml not taking part in mass drug administration programs. The subjects in this group were recruited previously for a study on the effects of albendazole of Loa loa microfilaraemia as described by Kamgno et al ., [ 45 ]. Serum samples from these Loa loa infected subjects were obtained from the Centre for research on filariasis and other tropical diseases, (CRFilMT), Yaoundé, Cameroon.…”
Section: Methodsmentioning
confidence: 99%